PRESERVASI DAN KONSERVASI NASKAH KOLEKSI MUSEUM NEGERI SONOBUDOYO YOGYAKARTA - , ERY SUSTIYADI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The manuscript collection at the Sonobudoyo Museum is very rare and irreplaceable. The collection has significant historic, educational, scientific, religious and cultural value. The manuscripts are also highly susceptible to damage as they are made from sensitive materials. To ensure that the manuscripts are preserved for use both today and in the future it is essential to carry out research on the conservation and preservation of this collection at the Sonobudoyo Museum The purpose of the research included: determining the physical condition of the manuscripts, measuring the environment in which they are stored, the causes of damage and an understanding of the present practices of preservation and conservation. This research will be used to prepare a Preservation and Conservation Management Plan for the term care of the collection at the Sonobudoyo Museum. The methodology used for the research included: a qualitative survey of the environmental conditions to determine if they are causing damage and a quantitative survey of the physical condition of the manuscripts including assessment of the physical damage of the binding, the condition of the paper, insect and fungal attack and damage due to the use of iron gall ink. The results of the survey for the manuscripts located in the store and the showcases will be compared to determine if the location of the items affects condition. The results of the research show that of the manuscripts located in the store 16.2 % are in very poor condition, 18.1% are in moderately poor condition and 65.6 % are in good condition. Whilst of the manuscripts located in the showcase 50 % are in moderately poor condition and 50 % are in good condition. The environmental conditions were measured using a data logger and the results showed that within the storage area there was the average temperature of 27.4 Â°C and the average relative humidity of 70.7 %. In the showcases the average temperature was 25.9 % and the average relative humidity is 77.5 %. All of these results are outside the recommended levels of temperature and RH in a museum and clearly indicate there are no environmental controls for temperature and RH at the Sonobudoyo Museum. Other results showed that 24.4 % were damaged by insects, 94.4 % showed signs of fungal damage and 13.7 % have damage due to the use of iron gall ink. The results indicate that even though preservation and conservation policies for the manuscripts have been implemented that the conditions are still not optimal. The manuscript collection at the Sonobudoyo Museum requires a Preservation and Conservation Management Policy. This policy needs to include aspects of preventive, passive and active conservation, restoration and a disaster management plan. The implementation of an effective management plan for this collection is essential for ensuring its long term preservation.